Educational Environment in Islamic Education - Fatarul Azmi; Abdi Sumarna; M. Ihsan Maulana (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2024)
An educational environment is very much needed in the educational process because the educational environment functions to support the teaching and learning process, a comfortable and supportive environment for the implementation of education is very much needed and also influences the achievement of the desired educational goals. Islamic education can run well when supported by a good environment. A comfortable environment that supports the implementation of education is very necessary and also influences the achievement of the desired educational goals.The educational environment includes all materials and stimuli that exist inside and outside the individual, both physiological, psychological and socio-qualitative. This research was conducted with the aim of knowing the educational environment in Islamic education. The method used in this research is literature study from various sources or references such as books and several other journals that discuss the same material. The research results show that in Islam, the educational environment is not only schools, but also families and communities which are necessary units in education. The results of this research also prove that a good educational environment in the family, school and community can be a barrier factor for children/students from getting trapped in bad behavior.